Quality Trends in Cocoa Commodity Exports and Prices from Indonesia Plantations - Ladi Wajuba Perdini Fisabilillah (Gorontalo Development Review, 2023)
One of the mainstay products of plantations, cocoa has a significant economic impact on the country, especially in terms of employment, income, and foreign exchange. This research aims to identify the relationships between cocoa exports and global cocoa prices between 1985 and 2020. Granger Causality was the quantitative methodology used in this research. Cocoa export volume and global cocoa prices are the study's factors. The study's findings showed that there was a one-way causal relationship between the variables, with the international cocoa price variable successfully affecting the cocoa export variable but no evidence of a causal relationship between the cacao export variable and the international cocoa price variable. This describes how coffee exports will be impacted by the price of coffee globally.